Association of Hemodynamic Instability with Periprocedural Stroke following Carotid Stenting (Bangladesh Journal of Neuroscience, 2026)
Background: Carotid stenting is a preventive treatment option for recurrence of stroke in ischemic stroke patients with carotid stenosis. Hemodynamic Instability including hypotension, bradycardia, hypertension are procedural complications during carotid stenting. It has an influence on periprocedural stroke. Aim of this study was to evaluate the association of hemodynamic instability with periprocedural stroke following carotid stenting.Methods: This Prospective longitudinal Study was conducted with 42 ischemic stroke patients with carotid artery stenosis at BSMMU from November 2020 to March 2022. The incidence of hemodynamic instability and stroke during periprocedural period following carotid artery stenting and subsequent 30 days follow up period were recorded. Then association of HI with periprocedural stroke was evaluated (p= < 0.05).Results: In this study, among 42 patients, severe carotid stenosis was 87.2% and ulceration was 64.1%. Hemodynamic instability was 33.3%. Among them, incidence of bradycardia, hypotension and hypertension was 28.2%, 25.6% and 2.6% respectively. Periprocedural stroke rate was7.1%. Association of hemodynamicin stability with periprocedural stroke after stenting was statistically not significant (p =>0.05).Conclusion: Hemodynamic Instability is not associated with periprocedural stroke following carotid stenting.